Analogical Framing: How Policy Comparisons Alter Political Support for Health Care Reform. Issue 5 (September 2020) - Barabas, Jason; Carter, Benjamin; Shan, Kevin
Analogies have captivated philosophers for millennia, yet their effects on modern public opinion preferences remain largely unexplored. Nevertheless, the lack of evidence as to whether analogies aid in political persuasion has not stopped politicians from using these rhetorical devices in public debates. To examine such strategic attempts to garner political support, we conducted survey experiments in the United States that featured the analogical arguments being used by Democrats and Republicans as well as some of the policy rationales that accompanied their appeals. The results revealed that analogies—especially those that also provided the underlying policy logic—increased support for individual health coverage mandates, the Affordable Care Act (ACA), and even single payer national health proposals. However, we demonstrated that rebutting flawed analogies was also possible. Thus, within the health care arena, framing proposals with analogies can alter policy preferences significantly, providing a way to deliver policy rationales persuasively.